DEBISS: a Corpus of Individual, Semi-structured and Spoken Debates - Souza, Klaywert Danillo Ferreira de; Pereira, David Eduardo; Campelo, Cláudio E. C.; Vasconcelos, Larissa Lucena (Anais do Simpósio Brasileiro de Tecnologia da Informação e da Linguagem Humana (STIL); 2025: Anais do XVI Simpósio Brasileiro de Tecnologia da Informação e da Linguagem HumanaDO - 10.5753/stil.2025.37860, 2025)
Debating is essential in daily life — whether in academic or professional settings, casual conversations, political forums, or online discussions. The range of debate applications is broad; therefore, their structures and formats can vary significantly. Developing corpora that account for these variations is challenging. The scarcity of debate corpora in the current state of the art, particularly for other languages beyond English, is notable. For this reason, this research proposes the DEBISS corpus, a collection of spoken and individual debates in Portuguese with semi-structured features. The corpus has broad applicability across Natural Language Processing tasks, including speech-to-text, speaker diarization, argument mining, and debate quality evaluation.